STRUKTUR DAN DINAMIKA POPULASI TERNAK KERBAU DI KECAMATAN ABUKI KABUPATEN KONAWE - Ariya Wijaksana Saputra; Achmad Selamet Aku; Muhammad Amrullah Pagala (Jurnal Peternakan (Jurnal of Animal Science), 2021)
The study aims to find out the structure and dynamics of natural growth of buffalo cattle in Abuki District of Konawe Regency using survey methods and location determination in proportion to sampling so that as many as 22 respondents obtained with research variables including the number of adult males, adult females, young males, young females, calves, birth rates, mortality, natural increase (Ni), expenditure figures and income figures. The data obtained is analyzed statistically to describe each variable studied. The results showed the number of buffalo cattle in Abuki Subdistrict 67 with adult male buffalo 19 (28,35%) adult females 17 (25,67%), young males 15 tails (22,38%) young females 14 tails (16,41%), 3 males (4,47%) 2-tailed female cubs (2,98%), birth percentage 41,66%, purchase 58,33%, deaths 12%, sales 12%, and natural increase 17,91%.